Electrical stimulation of the sciatic nerve restores inspiratory diaphragm function in mice after spinal cord injury - Walling, Ian; Baumgartner, Sarah; Patel, Mitesh; Crone, Steven A. (Frontiers in Neural Circuits, 2025)
IntroductionSpinal cord injury in the high cervical cord can impair breathing due to disruption of pathways between brainstem respiratory centers and respiratory motor neurons in the spinal cord. Electrical stimulation of limb afferents can increase ventilation in healthy humans and animals, but it is not known if limb afferent stimulation can improve breathing following a cervical injury.MethodsWe stimulated the sciatic nerve while using electromyography to measure diaphragm function in anesthetized mice following a cervical (C2) hemisection spinal cord injury, as well as in uninjured controls. The amplitude and frequency of inspiratory bursts was analyzed over a range of stimulation thresholds.ResultsWe show that electrical stimulation (at sufficient current thresholds) of either the left or right sciatic nerve could restore inspiratory activity to the previously paralyzed diaphragm ipsilateral to a C2 hemisection injury at either acute (1 day) or chronic (2 months) stages after injury. We also show that sciatic nerve stimulation can increase the frequency and amplitude of diaphragm inspiratory bursts in uninjured mice.DiscussionOur findings indicate that therapies targeting limb afferents could potentially be used to improve breathing in patients with cervical spinal cord injury and provide an experimental model to further investigate the neural pathways by which limb afferents can increase respiratory muscle activity.